STRATEGI GURU DALAM MENUMBUHKAN COMPETITIVENESS SISWA PADA MATA PELAJARAN IPS - Rahmania Ramadhani Dzikrullooh (Dinamika Sosial: Jurnal Pendidikan Ilmu Pengetahuan Sosial, 2026)
This study aims to analyze the planning of teacher strategies in fostering student competitiveness, the implementation of those strategies in the classroom, and the evaluation methods used by teachers to cultivate student competitiveness within Social Studies lessons. This study employs a qualitative approach with a field research design, conducted at MTs Bahrul Ulum Tambakberas, Jombang. Research subjects were selected through purposive sampling, including the headmaster, vice-head of curriculum, Social Studies teachers, and students actively involved in the learning process. Data collection techniques included observation, interviews, and documentation. Data validity was ensured through source and technique triangulation, while data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The research findings indicate that teacher strategy planning is carried out through the preparation of instructional tools, the setting of clear classroom goals, and the design of activities that encourage student participation and learning challenges. Furthermore, the implementation of these strategies is realized through interactive learning such as discussions, quizzes, and the provision of competitive stimuli capable of fully activating student engagement. Evaluation is utilized not only to measure learning outcomes but also as a foundation for reflection and the continuous improvement of instructional strategies. This study contributes to the strengthening of teaching practices in madrasas, the enrichment of academic studies at universities, and the development of Social Studies learning oriented toward student competitiveness. ABSTRAK Penelitian ini bertujuan untuk pertama, menganalisis perencanaan strategi guru dalam menumbuhkan competitiveness siswa, kedua menganalisis pelaksanaan strategi guru dalam menumbuhkan competitiveness siswa, dan strategi guru dalam mengevaluasi pembelajaran untuk menumbuhkan competitiveness siswa pada pelajaran IPS. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian lapangan. Lokasi penelitian di MTs Bahrul Ulum Tambakberas Jombang. Subjek penelitian dipilih melalui teknik purposive sampling, meliputi kepala madrasah, waka kurikulum, guru IPS dan siswa yang terlibat aktif dalam pembelajaran. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Keabsahan data diuji menggunakan triangulasi sumber dan teknik. Analisis data menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pertama, perencanaan strategi guru dilakukan melalui penyusunan perangkat pembelajaran, penetapan tujuan kelas yang jelas, serta perancangan aktivitas yang mendorong partisipasi dan tantangan belajar siswa. Kedua, pelaksanaan strategi diwujudkan melalui pembelajaran interaktif seperti diskusi, kuis, dan pemberian stimulus kompetitif yang mampu mengaktifkan keterlibatan siswa secara menyeluruh. Ketiga, evaluasi dimanfaatkan tidak hanya untuk mengukur hasil belajar, tetapi juga sebagai dasar refleksi dan perbaikan strategi pembelajaran secara berkelanjutan. Penelitian ini berkontribusi dalam penguatan praktik pembelajaran di madrasah, pengayaan kajian akademik di universitas, serta pengembangan pembelajaran IPS yang berorientasi pada daya saing siswa.